Absorption of deuterated water vapor in the 1.98 µm spectral region. (December 2021) - Régalia, L.; Capitaine, C.; Grouiez, B.; Mikhailenko, S.
Highlights: Analysis of deuterated water vapor absorption between 4850 and 5600 cm −1 . HITRAN2016 water line list versus laboratory observations. New line parameters of D2 16 O, D2 17 O, HD 16 O, and HD 17 O. Abstract: New spectra of water samples enriched by deuterium were recorded between 4500 and 5800 cm −1 using a Fourier transform spectrometer Bruker IFS 125HR combined to multi-pass cells. The spectra were recorded at room temperature with a non apodized resolution of 0.01 cm −1, using water evaporated from a D2 O+H2 O mixture in the liquid phase. The water vapor pressure was about 1.5 Torr and the absorption path was more than 100 m. A special attention was paid to the experimental procedure allowing to obtain HDO in the gas phase, and also to determine the partial pressure of all isotopologues. Synthetic spectra were compared to the observed ones. Numerous examples of disagreements between measurements and simulations using existing water line lists were observed for deuterated water species. Some lacks were found in the HITRAN2016 line list. A list of 580 transitions is reported that corrects erroneous and missing lines.